Flavonoid intake and its correlation to malondialdehyde serum among reproductive-aged women with obesity - Novi Silvia Hardiany; Wiji Lestari; Nina Indriyani Nasruddin (Indonesian Nutrition Association, 2022)
Background: Obesity modulates oxidative stress and can be detected by examining malondialdehyde (MDA) serum levels. Flavonoids are natural bioactive ingredients that can be found in various types of vegetables and fruits that function as antioxidants to suppress that oxidative stress. Objective: This study aimed to determine the correlation between flavonoid intake and MDA serum levels in obese women of reproductive age. Methods: This cross-sectional study was conducted in Kendari, Indonesia from April to October 2021. The purposive sampling method was used to obtain 88 subjects who met the research criteria. Data were collected through interviews covering flavonoids intake using validated SQ-FFQ. Anthropometric measurements were performed to assess nutritional status, and laboratory tests were applied to determine MDA serum levels. Results: The average intake of flavonoids in the subjects was 142,26 Â± 56,53 mg per day. Meanwhile, the average MDA serum level in the subjects was 2.16 mol/L, ranging from 1.09 nmol/ml to 6.71 nmol/ml. There was no significant correlation between total flavonoid intake and MDA serum levels in obese women of reproductive age (r=0,188, p=0,079). However, there was a weak correlation between the intake of flavonoid subclasses, namely flavan-3-ols/flavanols and MDA serum levels (r=0.325, p=0.002). Conclusion: We conclude that there was no correlation between total flavonoid intake and MDA serum levels. However, there was a correlation between flavan-3-ols/flavanols and MDA serum levels in the subjects.